Higher regularity for the Signorini problem for the homogeneous, isotropic Lamé system - Rüland, Angkana; Shi, Wenhui (Arxiv, 2021)
In this note we discuss the (higher) regularity properties of the Signorini problem for the homogeneous, isotropic Lam\'e system. Relying on an observation by Schumann \cite{Schumann1}, we reduce the question of the solution's and the free boundary regularity for the homogeneous, isotropic Lam\'e system to the corresponding regularity properties of the obstacle problem for the half-Laplacian.
Gesehen am 27.05.2021